Pengaruh Persepsi Mutu Pelayanan Kesehatan Terhadap Kepuasan dan Minat Berkunjung Kambali Pasien Rawat Jalan di Puskesmas Kecamatan Duren Sawit - Marsono Marsono; Elwindra Elwindra (STIKes Persada Husada Indonesia, 2016)
Quality of community health centre service is considered by the the health service that is able to create patient’s satisfaction targetted by the health centre. Based on the results of earlier survey conducted by the researcher at Puskesmas Duren Sawit, it was found that there is still pasient’s cummulation at waiting room of admission. This showed the poor given service quality. This study aimed to explain the perception influences of service quality dimensional that consists of physical proof, reliability, responsiveness, guarantee and certainity, and the empathy towards the satisfaction and interest of the outpatients to revisit Puskesmas Duren Sawit year 2016. The population in this study were 99 patients utilizing outpatient services on July 2016. Data was collected using questionares and analysed with Univariate, Bivariate and IPA (Importance Performing Analysis) tests with a tangible standard of 0,05. Study results showed no significant influence between respondents’ characteristic against level of satisfaction and interest for revisits. The variables that showed the presence of influence were Responsiveness, and Tangible with P-value of <0,05. In this study, level of satisfaction also held a significant relationship towards revisting interest with P-value of <0,05. Thus it is hoped that Duren Sawit district health centers maintain Dimensional Quality that as satisfactory increasing outpatient’s satisfaction and interest in returning to Duren Sawit district health centers for the year 2016. Tangible elements deemed to affect customer satisfaction, including a very important element, but management has not done in accordance with the wishes of the customer, so that was disappointing or not satisfied, that is considered as the main priority issues.